2010
DOI: 10.1097/hnp.0b013e3181d39ade
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual and Alternative Healthcare Practices of the Amish

Abstract: Although the use of spiritual and alternative healthcare practices is increasing, knowledge of these practices among the Amish is limited. This study explored the spiritual and healthcare practices of 134 Amish. Information about the diversity and prevalence of these practices among the Amish may be useful to nurses in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…The use of herbal products and nutritional supplements reflects their belief in the provision of God to give them what they need to be healthy, as well as their caution about using mainstream medicine. This finding is consistent with those of previous studies that noted Anabaptist community members often sought to limit drug use and rely on natural products to prevent or treat illnesses (Garrett-Wright et al, 2016;Sharpnack et al, 2010). This finding is also congruent with a survey conducted by Rohr et al (2019) that found only about 36% of participants sought out doctors as an important source of information on health issues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The use of herbal products and nutritional supplements reflects their belief in the provision of God to give them what they need to be healthy, as well as their caution about using mainstream medicine. This finding is consistent with those of previous studies that noted Anabaptist community members often sought to limit drug use and rely on natural products to prevent or treat illnesses (Garrett-Wright et al, 2016;Sharpnack et al, 2010). This finding is also congruent with a survey conducted by Rohr et al (2019) that found only about 36% of participants sought out doctors as an important source of information on health issues.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Gesink and colleagues (2017), a strong interest in basic health tenets such as obtaining adequate sleep and maintaining a good diet were reported. Other authors have noted the predisposition of Anabaptists to use herbal products and supplements to prevent and treat illness instead of seeking formal health care services (Gingrich & Lightman, 2006;Sharpnack et al, 2010). Anabaptists seek to maintain their health so they can continue to work and be active in their community (Armer & Radina, 2006;Fisher, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Anabaptist populations generally prefer to prevent or treat health problems with home remedies and herbal products (Gingrich and Lightman 2006). In one study, 85% of subjects reported the use of alternative healthcare practices with supplements or herbal products (Sharpnack, Griffin, Benders, and Fitzpatrick 2010). However, Anabaptist community members are willing to seek professional medical help from English communities when needed (Gingrich and Lightman 2006) with many Old Order communities utilizing modern medical services and alternative treatments concurrently (Wenger 1995).…”
Section: Background Literaturementioning
confidence: 99%
“…The term Gelassenheit, meaning yielding to God's authority, guides Amish behaviors (Weyer et al, 2003). Other research with Amish communities support the heavy influence of their faith in God on their health beliefs and decisions (Gerdner, Tripp-Reimer, & Sorofman, 2002;Sharpnack, Griffin, Benders, & Fitzpatrick, 2010). Families in this study recognized that the ultimate fate of a child's health is in the hands of God rather than the health care system.…”
Section: Presence Of God In Health Decisionsmentioning
confidence: 66%
“…Previous research supports that Amish families use vitamin and herbal remedies, in addition, to the use of manual healing, such as chiropractic and reflexology, or "powwowing" referring to the use of words or charms by an Amish healer called a brauche (Blair & Hurst, 1997;Gerdner, Tripp-Reimer, & Sorofman, 2002;Sharpnack, Griffin, Benders, & Fitzpatrick, 2010;von Gruenigen et al, 2001;Wenger & Wenger, 2003). This study supports the use of home remedies as well as manual healing treatments such as chiropractic and reflexology.…”
Section: Using Folk and Popular Remedies As Treatmentmentioning
confidence: 99%